2011
DOI: 10.3109/15563650.2010.547860
|View full text |Cite
|
Sign up to set email alerts
|

White phosphorus poisoning by oral ingestion of firecrackers or little devils: Current experience in Ecuador

Abstract: The typical case was an adolescent woman between 16 and 19 years with self-harm around Christmas. There was no specific treatment, but early attendance was associated with improved prognosis. Further studies are necessary to establish an adequate protocol of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The myelosuppression selectively involving the myeloid series and sparing other lineages as seen in our case, was not reported by Tafur et al 9 A more recent study from Ecuador reported that apart from vomiting, diarrhoea, and abdominal cramps, abnormal liver enzymes and coagulation times were the major clinical features of yellow phosphorus toxicity. 13 However, no abnormalities of blood counts or bone marrow suppression were reported by the authors.…”
Section: Discussionmentioning
confidence: 89%
“…The myelosuppression selectively involving the myeloid series and sparing other lineages as seen in our case, was not reported by Tafur et al 9 A more recent study from Ecuador reported that apart from vomiting, diarrhoea, and abdominal cramps, abnormal liver enzymes and coagulation times were the major clinical features of yellow phosphorus toxicity. 13 However, no abnormalities of blood counts or bone marrow suppression were reported by the authors.…”
Section: Discussionmentioning
confidence: 89%
“…Also, decreased ventricular contractility has been reported [2]. In a cross sectional study where 85 patients were studied, dysrhythmias were noted in only two patients, another four showed tachybradycardia [8]. Damage to myocardium on post mortem histological examination was seen in a number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Cardiac toxicity includes hypotension, tachycardia, arrhythmias, and cardiogenic shock (9) .Alteration in ECG such as inverted T waves, changes in QRS complex, tachycardia, arrhythmias and decreased ventricular contractility has been reported (8) . In a cross sectional study where 85 patients were studied, dysrhythmias were noted in only two patients, another four showed tachy-bradycardia (10) . Damage to myocardium reported in studies included fatty infiltration of the muscle, markedly dilated heart chambers, and necrosis of myocardium (8) .…”
Section: Discussion:-mentioning
confidence: 99%